Numerical Analysis of Heat Transfer Enhancement of Solar Air Heater using Discrete Triangle Wave Corrugations. Issue 1 (31st December 2022) - Sharma, Vansh Ratna; S, Sai Sankalp; Fernandes, Dolfred Vijay; M S, Manjunath
Abstract: Enhancement of heat transfer in solar air heater systems using corrugations has the dual benefit of enhanced heat transfer area and enhanced flow turbulence. This work presents two-dimensional computational fluid dynamics (CFD) analysis to evaluate the effect of discrete triangle wave corrugations on the absorber plate for different flow Reynolds numbers of 6000–24000. The geometric parameters of corrugation such as the non-dimensional amplitude ( A = 0.025, 0.05 and 0.1) and non-dimensional wavelength ( WL = 0.113, 0.226 and 0.453) are varied to establish the thermo-hydraulic performance. The CFD results reveal that the presence of discrete triangle wave corrugations significantly affect the flow structure near the absorber surface and exhibit enhanced fluid turbulence levels. The highest increase in the Nusselt number is found to be about 2.082 times higher than that of the smooth duct for A = 0.1 and WL = 0.453 at Re = 6000. The maximum rise in friction factor is about 2.568 times that of the smooth duct at Re = 6000 for the configuration of WL = 0.113 and A = 0.1. The configuration having A = 0.1 and WL = 0.453 can be particularly useful for lower flow rate requirements and exhibits the highest thermal enhancement factor (TEF) of about 1.612 at Re = 6000 among all the configurations considered in the present study. However, the configuration having A = 0.05 and WL = 0.453 provides a relatively steady TEF performance for a wider range of flow rates with a maximum TEF of 1.473 at Re = 12, 000.